Igapó (Black-water flooded forests) of the Amazon Basin (Springer International Publishing, 2018)
Igapó forests are a common part of the Amazon whose ecosystems are critical to our shared human future. The introduction addresses the structure, function and dynamics of igapó forests in the Amazon basin, focusing on their uniqueness due to their high level of complexity defined as the many ways that different components of igapó forests in the Amazon basin ecosystem interact and also on how those interactions are on a higher-order compared to other tropical forests. The text then breaks down the igapó ecosystem using these sections: (1) Igapó forests over space and time, (2) Water, light and soils, (3) The carbon cycle, (4) Litter, fungi and invertebrates, (5) Vertebrates, (6) Plant population studies, (7) Plant community studies, and (8) Human impacts and management. Experts from around the world serve as chapter authors that review what is known about their specific part of the igapó ecosystem, what research they have done, and also what needs to be done in the future. .